2021
DOI: 10.1002/jmv.27444
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ABO and Rhesus blood groups on COVID‐19 susceptibility and severity: A case‐control study

Abstract: Early evidence from China suggested that blood groups may be involved in susceptibility to COVID-19. Several subsequent studies reported controversial results.We conducted a retrospective matched case-control study that aims to investigate the association between blood groups and the risk and/or severity of COVID-19.We compared the blood groups distribution of 474 patients admitted to the hospital for COVID-19 between March 2020 and March 2021, to that of a positive control group of outpatients infected with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
0
11
0
4
Order By: Relevance
“…While a recent population-based cohort study from Ontario, Canada, demonstrated that Rh-negative individuals may be linked with a slightly lower risk for SARS-CoV-2 infection and severe COVID-19 illness [19]. In October 2021, a similar study performed in Beirut, Lebanon, with a sample size of 404 patients concluded that A Rh+ blood group is associated with an increased risk of developing COVID-19 [20].…”
Section: Introductionmentioning
confidence: 99%
“…While a recent population-based cohort study from Ontario, Canada, demonstrated that Rh-negative individuals may be linked with a slightly lower risk for SARS-CoV-2 infection and severe COVID-19 illness [19]. In October 2021, a similar study performed in Beirut, Lebanon, with a sample size of 404 patients concluded that A Rh+ blood group is associated with an increased risk of developing COVID-19 [20].…”
Section: Introductionmentioning
confidence: 99%
“…We did not find any other associations between blood groups and SARS‐CoV‐2. This questions the validity of previous findings of an association to the Rh blood group 11,12,14,15 …”
Section: Discussionmentioning
confidence: 72%
“…This questions the validity of previous findings of an association to the Rh blood group. 11,12,14,15 Two COVID-19 severity results worth discussing are blood type O vs AB, which was significant (p = .008), and secretor status, which was close to being significant (p = .06). Blood type AB is a rare phenotype (5%), which reduces confidence in that result.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“… 20 Kerbage et al (2022) indicated that A Rh (+) subjects are more susceptible to SARS-CoV-2 infection; however, ABO blood groups lack any association with the severity of the disease. 21 Supporting the Indian study, Behera et al (2022) emphasized that blood group A was the most sensitive group considering a higher risk severity of the disease with admission to the intensive care unit. 19 In the present study, a total number of 18,639 (297 COVID-19 patients and 18,342 controls) individual's current data were investigated including SARS-CoV-2 RT-PCR results, sex, age, ABO blood groups, and Rh blood types.…”
Section: Discussionmentioning
confidence: 98%